Shrinking agricultural land and changing livelihoods after land acquisition in Vietnam - Tran Tuan Nguyen (Bulletin of Geography. Socio-Economic Series)
The phenomenon of agricultural land shrinkage is widespread in the world. This phenomenon has many causes, of which industrialisation is one. The industrialisation process is supported in most countries by the use of land acquisition as a tool to convert land use from agricultural to non-agricultural. This research surveyed 100 land-lost households to examine the impact of farmland shrinkage on their livelihoods in Vietnam. The study focuses on three factors: employment and income, how compensation money is used, and quality of life after land loss. The results show that revenue increased by USD 1,500 per household compared to before. The rate of employment depends on age and gender. There is a drop in employment among women over 35 years old and men over 40. The use of compensation money focuses on non-farm goals, with the bright spot being an investment in education for future generations. The environment and society tend to be worse according to the subjective assessment of households, but their ultimate choice is still to enjoy life after land acquisition.